Brain Metastasis as Initial Manifestation of Melanoma (A Case Report) - Santos, Vitorino M.; Silva, Renata F.; Passini, Viviane V.; Duarte, Mayza L.; Flores, Leandro P. (BALI MEDICAL JOURNAL, 2016)
Background: Melanoma is a malignancy derived from the neural crest, constituted of melanocytes  found in the basal layer of epidermis, with the main function of melanin production. Case: A 64-yearold woman was admitted with headache and dyslalia and reported some episodes of vertigo and falls  in the last six months. A superficial red and dark skin discoloration in the scalp and a node in the right  parotid gland were observed. Computed tomography of the brain showed nodular lesions in the left  parietal and right temporal and occipital lobes with hemorrhagic features, in addition to mass effect.  Furthermore, PET-CT images were suggestive of brain, lung, and adrenal metastasis. The patient  evolved with intracranial hypertension and a neurosurgery was performed. Histopathological and  immunohistochemistry studies revealed metastatic melanoma. Conclusions: She underwent schedules  of radiation therapy and chemotherapy, but developed uncontrolled sepsis and died in spite of clinical  management and intensive care support. Cutaneous primary site of this malignancy in the scalp was  previously neglected; therefore, neurological disturbances were the initial manifestations of  melanoma. Immunohistochemistry findings allowed ruling out the main differential hypotheses.
Keywords: Brain metastasis, immunohistochemistry diagnosis, melanoma.